Tsunami simulation due to seaquake at Manila Trench and Sulu Trench - Mardi, N.H. (Springer Netherlands, 2017)
Seaquake is a phenomenon where there are water disturbance at the sea, caused by earthquake or submarine eruption. The scope of this study focuses on tsunami simulation due to Manila Trench and Sulu Trench seaquake which is prone to harm Malaysia offshore areas. Manila Trench is a highly potential earthquake source that can generate tsunami in South China Sea. Meanwhile, Sulu Trench could be a threat to east of Sabah offshore areas. In this study, TUNA-M2 model was utilized to perform tsunami simulation at South China Sea and Sulu Sea. TUNA-M2 model applied Okada source model to create tsunami generation due to earthquake. It utilized linear shallow water equation during tsunami propagation with its radiant boundary condition. Five simulations performed at each study region. Forecast points at South China Sea areas were divided into three separate locations which are at the Peninsular Malaysia, west of Sabah and Sarawak offshore areas. Forecast points at Sulu Sea were focused at the east of Sabah offshore areas. This paper will present the simulation results of tsunami wave height and arrival time at various forecast points. The findings of this study show that the range of tsunami wave height at Sulu Sea is higher than that of South China Sea. The tsunami arrival time at Sulu Sea is less than South China Sea. It can be concluded that Sulu Sea poses worse tsunami threat than South China Sea to the Malaysian offshore areas. © 2016, Springer Science+Business Media Dordrecht.